Chán Buddhism in Dūnhuáng and Beyond : A Study of Manuscripts, Texts, and Contexts in Memory of John R. McRae - Anderl, Christoph; Wittern, Christian (Religious Studies, Theology and Philosophy E-Books Online, Collection 2020, ISBN: 9789004419094., 2021)
Chán Buddhism in Dūnhuáng and Beyond: A Study of Manuscripts, Texts, and Contexts in Memory of John R. McRae is dedicated to the memory of the eminent Chán scholar John McRae and investigates the spread of early Chán in a historical, multi-lingual, and interreligious context. Combining the expertise of scholars of Chinese, Tibetan, Uighur, and Tangut Buddhism, the edited volume is based on a thorough study of manuscripts from Dūnhuáng, Turfan, and Karakhoto, tracing the particular features of Chán in the Northwestern and Northern regions of late medieval China.